Klub belogo popugaia . Klub belogo popugaia . The White Parrot's Club . Клуб белого попугая - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Informal meeting of film and theater actors with storytelling and jokes. Featured in the program: Gurchenko, Liudmila Markovna (Actress) Contributors: Riazanov, El'dar (Anchor); Nikulin, IUrii Vladimirovich (Anchor) Неформальная встреча актеров театра и кино, c рассказами историй и анекдотов. В программе участвуют: Гурченко, Людмила Марковна (Актриса) Создатели: Рязанов, Эльдар (Ведущий/Ведущая); Никулин, Юрий Владимирович (Ведущий/Ведущая)